The perception of thermal comfort in Malaysia public low-cost housing / Kelvin Yong, Zanaibi Abdullah and Nazli Che Din - Yong, Kelvin; Abdullah, Zunaibi; Che Din, Nazli (UiTM Press, 2021)
In Malaysia, the thermal comfort of low-cost high-rise housing has not been widely given a significant emphasis in the qualitative study despite its increasing scale and significance in the urban areas. Occupant’s perception and adaptive behaviour are important to achieve the level of satisfaction in terms of a comfortable living environment. This paper assesses the occupants’ perception and behaviour in a low-cost high-rise housing development that has been argued with various problems which have a considerable impact on lifestyle. Understanding of comfort as social and cultural behaviour, rather than an engineering approach. This research shows the results of a pilot study that utilized a qualitative strategy for analysing thermal comfort, rather than using the standard thermal comfort research methodologies. The building of study, in the category of low-cost high rise residential located at the urban context of Kuala Lumpur housing area, which is mainly natural ventilated with a versatile adaptive possibility available for the occupants. The outcomes signify the adaptive behaviour that enhances or limit the thermal comfort-related varieties. The results from the pilot study direct for more extensive research and comparison with previous qualitative studies.